Lições da COVID-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? - Siúta, Moisés (Desafios para Moçambique 2021, 2021)
O presente artigo procura discutir lições que se podem tirar em relação ao papel da poupança para Moçambique, no âmbito da pandemia da COVID-19. O artigo inspira-se na pesquisa sobre poupança, pobreza e protecção social desenvolvida pelo Instituto de Estudos Sociais e Económicos (IESE), que estabelece a ligação entre poupança e protecção social, tendo em vista estudar mecanismos que permitam desenvolver um sistema de protecção social financeiramente viável em Moçambique (Siúta, 2019b). O objectivo deste artigo é estabelecer a ligação entre a poupança e a COVID-19, discutindo o seu papel no âmbito da resposta à pandemia. A metodologia usada, além da revisão de literatura, inclui a exploração de dados sobre a evolução da pandemia em diversos países, fornecidos pela Organização Mundial da Saúde (OMS/WHO (World Health Organization)), cuja base de dados foi preparada e disponibilizada publicamente por Ritchie et al. (2020). Para completar a análise através da exploração de dados sobre a economia dos países, analisando, principalmente, a evolução da poupança doméstica e do produto dos países, recorreu-se à base de dados dos indicadores de desenvolvimento dos países, disponibilizada pelo Banco Mundial (World Bank, 2021). O artigo, incluindo a presente introdução, subdivide-se em quatro secções. Nas secções a seguir, na primeira, discute-se a relevância da poupança doméstica, no contexto da pandemia da COVID-19, com base numa abordagem teórica da poupança; a segunda secção, baseada em dados sobre a poupança doméstica e a capacidade de testagem e vacinação contra a COVID-19, procura discutir a relevância da poupança doméstica nos países ao redor do Mundo, incluindo o caso de Moçambique. Na última secção, apresenta-se uma breve discussão sobre o contexto moçambicano e a relevância da poupança doméstica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; poverty / pobreza; social protection / proteção social; society / sociedade

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Improving Health for the Poor in Mozambique: The Fight Continues - Chao, Shiyan; Kostermans, Kees (International Bank for Reconstruction and Development / The World Bank, 2002)
The health sector in Mozambique has made significant progress in terms of increasing coverage of services. However, health remains a major concern in the area of poverty reduction. The study describes the health status of the population, especially of the poor, and how the sector responds to the needs. Huge inequalities continue to exist with regards to resource allocation, deployment of staff and availability of services among various geographic areas, between the urban and rural population, and between the poor and the non-poor. The study builds upon the existing studies on health and consolidates the sector knowledge. Based on the analysis, the study makes various recommendations on how the health sector reforms can be made more pro-poor by focusing on certain interventions, by targeting certain areas and population groups, by designing new delivery models that would bring the services closer to the population, and by improving financial management to serve the poor more effectively.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; health / saúde; poverty / pobreza